A novel smart handpiece controlled by voice command system - Adam Malik Hamudeng; Nurul Auliya; Andi NT. Sapada; Muhammad N. Rachmat (DiscoverSys Inc., 2021)
Objective: To investigate the possibility of Smart Handpiece